RELIABILITY ANALYSIS OF ACTIVE REDUNDANT SYSTEM USING GEOMETRIC DISTRIBUTION - Pankaj,; Bhatti, Jasdev; Mohit Kumar kakkar, (Malaysian Journal of Science, 2022)
The present paper is an initiative taken towards study and analysis of industries concerning different maintenance strategies towards their products on behalf of their working and maintenance level. The objective of presenting the concept of the dual nature of repair for units having extra or major failures in addition to regular ones is well explained. The stochastic analysis of reliability characteristics using regenerative techniques for the system consisting of two parallel units following the active-standby redundancy and having different repair time distributions was also studied using geometric distribution. The numerical equations and results are being evaluated for reliability parameters like mean time to system failure, availability of the system in operative form, down period of the system following repair mechanism using regenerative techniques, and geometric distribution. The graphical analysis has also been presented for-profit function with respect to repair and failure rate.